Cancer Research in Translation Ovarian and Peritoneal Neoplasms: Comprehensive Review - Kazmi, Samreen; Anjaneyulu, M. (Asian Pacific Journal of Cancer Nursing, 2025)
Ovarian Cancer is a leading cause of death in Women often diagnosed at the late stage due to several factors generally due to its asymptomatic nature until the disease is advanced. Symptoms can be similar to other conditions, such as irritable bowel syndrome or menopause. Often Ovarian Cancer spread through omentum as the cells directly invade the omentum from the ovarian tumour. In this process the cells can break away from ovarian tumour and spread through peritoneum fluid, implanting on the omentum which is rich of blood supply, making it a fertile ground for cancer cells to grow. Omentum involvement is a common feature of advanced ovarian cancer often making surgical debulking complicated. This review aims to summarize the current understanding of the relationship between the peritoneal Neoplasms and ovarian cancer highlighting the molecular mechanisms, clinical implications and potential therapeutic strategies. Peritoneal neoplasm is a type of carcinomatosis where cancer cells spread through the peritoneum originating mostly from other cancers. Cancer cells can also spread to the omentum through lymphatic system. The relationship between peritoneum cancer and ovarian cancer is complex, involving various molecular mechanisms and cellular interactions.